A conceptual model for the measurement of the expected value of a supply chain relationship. (1st January 2013) - Keebler, James S.; Hill, Craig A.; Joo, Seong-Jong
The objective of this research paper is to describe a conceptual framework for evaluating the expected value of supply chain relationships (EVSCR). Various types of supply chain relationships are defined in the literature. Then borrowing basic valuation concepts from finance theory, a supply chain relationship valuation model is developed. Valuation components and synergy effects are quantified along two dimensions of the relationship – resource complementarity and cooperative effectiveness. The EVSCR model permits the categorisation of five types of business connections and suggests strategies to improve relationships. Firms can predict the value of potential supply chain relationships, better describe the value of existing relationships, and make informed decisions for management action to improve marginal relationships. This valuation framework is new to the supply chain literature and serves to expand the set of tools available to planners and managers to quantify existing and desirable supply chain relationships needed to improve supply chain performance.